Lo criollo-antillano en la novela Chimères d’En-Ville de Raphaël Confiant - Senior Grant, Alder (2013)
This article attempts to analyze three fundamental aspects that mark the novel Chimères d’En-Ville, written by Raphaël Confiant, a prolific contemporary author from Martinique (end of the twentieth century and beginning of this era): first, it explores the opposition French language versus Creole language; next, the different senses or significations of black color; ending finally with the contrast between city and country in this fictional francophone work.